On the road to global labour history : a festschrift for Marcel van der Linden - Linden, Marcel van der, 1952-; Roth, Karl Heinz (Historical materialism book series, 2017)
Global Labour History has firmly established itself in the past three decades. This anthology provides an overview of the conceptual aspects of the discipline and is underpinned by case and field studies from Africa, Latin America, the Middle East and China. It is dedicated to Marcel van der Linden, the doyen of, and networker for, Global Labour History.--